The role of teamwork in developing health awareness among secondary school students: A field study in the city of Baghdad - Alwan, Zahraa; Muhammad, Rasool Mutlaq (Al-Adab Journal, 2023)
In our study، we look forward to studying the role of social work in developing health awareness within schools in Iraqi societyThe objectives of this study were determined to reveal the extent of the contribution of school social work in guiding students towards a sound health status، and to know the role of school social work in promoting awareness among students about the most prominent health problems that the student may be exposed to at this stage and knowing his role in educating the staff Educational in the prevention of health problems، and knowledge of the impact of health problems on the student’s academic level، the type of study is descriptive field study that relied on collecting The necessary data and information about the study community، and this was done by using the social survey method and adopting some data collection tools such as questionnaire، observation and interview in order to collect accurate information.